Nonlinearities in Source Receptor Relationships for Sulfur and Nitrogen Compounds - Fowler, David; Muller, Jennifer; Smith, Rognvald I.; Cape, John Neil; Erisman, Jan Willem (Ambio, 2005)
The relationship between emissions and deposition of air pollutants, both spatially and in time forms an important focus for science and for policy makers. In practice, this relationship may become nonlinear if the underlying processes change with time, or in space. Nonlinearities may also appear due to errors in emission or deposition data, and careful scrutiny of both data sources and their relationship provides a means of picking up such deficiencies. Nonlinearities in source receptor relationships for sulfur and nitrogen compounds in Europe have been identified in measurement data for the UK. In the case of sulfur, the dry deposition process has been shown to be strongly influenced by ambient concentrations of NH3, leading to substantial increases in deposition rate as SO2 concentrations decline and the ratio SO2/NH3 decreases. The field evidence extends to measurements over three different surfaces in three countries across Europe. A mechanistic understanding of the cause of this nonlinearity has been provided. Apparent nonlinearities also exist in the sulfur deposition field through the influence of shipping emissions. The effect is clear at west coast locations, where during a period in which land-based sulfur emissions declined by 50%, no significant decline in concentrations of SO42− in precipitation were observed. The sites affected are primarily the coastal regions of southwestern UK, where shipping sources contribute a substantial fraction of the deposited sulfur, but the effect is not detectable elsewhere. Full quantification of the spatially disaggregated emission and their changes in time will eliminate this apparent nonlinearity in the source—receptor data. For oxidized nitrogen emission and deposition in the UK, there is strong evidence of nonlinearity in the source—receptor relationship. The concentrations and deposition of NO3− in precipitation have declined little following a reduction in emissions of 45% during the period 1987 to 2001. The data imply a significant decrease in the average transport distance for oxidized nitrogen and most probably an increase in the average oxidation rate. However, the net effect of changes in aerosol chemistry due to changes in sulfur emissions and less competition for the main oxidants as a consequence of reductions in sulfur emission have not been separated. A quantitative explanation of the cause of this nonlinearity is lacking and the effects are therefore identified as an important uncertainty for the development of further protocols to control acidification, eutrophication and photochemical oxidants in Europe.